The translation of the Chinese Civil Code in a perspective of comparative law - Herbots, Jacques Henri (Comparative Legilinguistics, 2023)
Observing the phenomenon of the translation of statutory texts in China, it is noteworthy that the source language was mainly German until after the plethoric legislation under Deng Xiaoping. Then the pendulum swung back. Chinese is now the source language and statutes are translated into English. What is for a Chinese Court the legal value of the translation of a legal text, for instance of a disposition of the Civil Code? A difference has to be made between an authentic translation, and an official or a private one. Only in the hypothesis that both language versions are authentic, the court will have the obligation to reconcile them in case of divergence between them. For a court having to apply a particular disposition of a statute in a pending case – or for an arbitrator, a legal counsel or a scholar – the practical value of a translation is that the interpretation by the translator himself of the text which has to be translated (even a non-authentic translation), can influence and facilitate their subsequent interpretations by others. If made timely, it could also help the legislator to draft a clearer final text. The same is true for the drafter of a treaty or of a commercial contract. The obvious negative aspect of a translation is that it can contain errors and can by consequence create confusion and misunderstanding by those who later on will have to apply the disposition. Some examples hereof can be found in the Chinese Civil Code. Two recommendations can in conclusion be made, one concerning the moment of the translation, and one concerning a desirable supervision by a comparative lawyer during the translation process.